Habilidades sociales y convivencia escolar en estudiantes de segundo grado de secundaria en la Institución Educativa Mariscal Oscar R. Benavides, distrito de Iquitos 2019 - Grandez Ruiz, Karen Gilma (2023)
The objective of the research was: To determine the relationship between social skills and school coexistence in 2nd grade high school students at the Mariscal Oscar R. Benavides Educational Institution, Iquitos - 2019. The research was of a confirmatory type, with a non-specific design. experimental descriptive - correlational cross-sectional study, made up of a population of 453 students in the second grade of high school, and a sample of 208 students selected in a stratified manner by proportional affixation and simple random, who were administered two questionnaires to measure the variables study. The results obtained on the level of social skills, allowed to determine that of 100% (208 students), 34.6% (72) reported a good level; 44.2% (92) a Regular level; and 21.2% (44) a Deficient level. Regarding the results obtained on the school coexistence variable, it was determined that of 100% (208 students), 33.7% (70) reported an Adequate level; 45.2% (94) an Inadequate level; and 21.1% (44) an Inadequate level. Finally, this investigation, after the application of Kendall's ?-b non-parametric statistical test, concluded that there is a significant relationship between social skills and school coexistence in second grade students at the Educational Institution Mariscal Oscar R. Benavides, Iquitos 2019, being demonstrated the hypothesis of investigation raised in the present investigation (p = 0.0000, p < 0.05).